Asthma: A Risk Factor for Dental Caries? - Thomas, MS; Parolia, A; Kundabala, M (Journal of Nepal Paediatric Society, 2010)
This report points out a correlation between asthma and dental caries. It also gives certain guidelines on the measures to be taken in an asthmatic to negate the risk of dental caries. Key words: Asthma, Caries risk, Caries prevention, Dental caries DOI: 10.3126/jnps.v30i3.3929 J Nep Paedtr Soc 2010;30(3):175-176